2017
DOI: 10.1016/j.jacc.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Transcatheter Aortic Valve Replacement for Bicuspid Versus Tricuspid Aortic Valve Stenosis

Abstract: Compared with tricuspid AS, TAVR in bicuspid AS was associated with a similar prognosis, but lower device success rate. Procedural differences were observed in patients treated with the early-generation devices, whereas no differences were observed with the new-generation devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
246
5
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 384 publications
(267 citation statements)
references
References 32 publications
10
246
5
6
Order By: Relevance
“…[43][44][45] The Bicuspid Transcatheter Aortic Valve Replacement Registry is the largest international, multicenter, observational registry that enrolls all consecutive patients with bicuspid AS from Europe, North America, and Asia-Pacific regions. 44,45 In the published studies, TAVR devices were divided into early generation (Sapien XT, Edwards Lifesciences, Irvine, California; CoreValve, Medtronic, Minneapolis, Minnesota) versus new generation devices (Sapien 3, Edwards Lifesciences, Irvine, California; Lotus, Boston Scientific, Marlborough, Massachusetts; Evolut R, Medtronic, Minneapolis, Minnesota). Implantations of new generation devices were less likely to result in residual moderate to severe paravalvular leak, annulus rupture or second valve-in-valve implantation.…”
Section: Transcatheter Aortic Valve Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] The Bicuspid Transcatheter Aortic Valve Replacement Registry is the largest international, multicenter, observational registry that enrolls all consecutive patients with bicuspid AS from Europe, North America, and Asia-Pacific regions. 44,45 In the published studies, TAVR devices were divided into early generation (Sapien XT, Edwards Lifesciences, Irvine, California; CoreValve, Medtronic, Minneapolis, Minnesota) versus new generation devices (Sapien 3, Edwards Lifesciences, Irvine, California; Lotus, Boston Scientific, Marlborough, Massachusetts; Evolut R, Medtronic, Minneapolis, Minnesota). Implantations of new generation devices were less likely to result in residual moderate to severe paravalvular leak, annulus rupture or second valve-in-valve implantation.…”
Section: Transcatheter Aortic Valve Replacementmentioning
confidence: 99%
“…Cumulative event rates for all-cause mortality were similar between bicuspid and tricuspid aortic valves. 45 Despite the foregoing data, selection bias nearly always exists whereby TAVR was generally performed in highrisk or inoperable bicuspid AS patients. In addition, bicuspid AS patients are more likely to be younger, [43][44][45] and the long-term implications of age-related progressive aortic dilatation and its complications need to be included in the decision-making process.…”
Section: Transcatheter Aortic Valve Replacementmentioning
confidence: 99%
“…Two recent studies on early generation TAVI devices showed a higher incidence of THV malposition requiring multiple THVs implantation (7.2%) and moderate or severe PVR that was found in 28.4 and 15.9% of patients, respectively [10,11]. In a large multicenter propensity-based analysis comparing TAVI outcomes in bicuspid aortic valves versus tricuspid aortic valves, Yoon et al [11] showed that among the early generation THV group, TAVI in patients with bicuspid AS was complicated more frequently with aortic root injury, mainly related to the Sapien XT implantation, implantation of more than one THV and moderate or severe paravalvular regurgitation, mainly related to the CoreValve implantation.…”
Section: Tavi In Bicuspid Aortic Valvesmentioning
confidence: 99%
“…In a large multicenter propensity-based analysis comparing TAVI outcomes in bicuspid aortic valves versus tricuspid aortic valves, Yoon et al [11] showed that among the early generation THV group, TAVI in patients with bicuspid AS was complicated more frequently with aortic root injury, mainly related to the Sapien XT implantation, implantation of more than one THV and moderate or severe paravalvular regurgitation, mainly related to the CoreValve implantation. Among the group treated with the new generation devices, however, there were no significant differences in procedural outcomes between bicuspid and tricuspid valves.…”
Section: Tavi In Bicuspid Aortic Valvesmentioning
confidence: 99%
See 1 more Smart Citation